2023
DOI: 10.3390/agronomy13092440
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Absorption and Desorption by Biochar

Zijian He,
Chao Wang,
Hongxia Cao
et al.

Abstract: Biochar is a potential solution for addressing environmental problems related to excessive nitrogen (N). However, there is still some debate about the absorption and desorption of nitrate nitrogen (NO3−-N). Therefore, this study investigated the NO3−-N adsorption and desorption performance onto biochar and biochar-soil mixture to address this gap. The results showed that the biochar produced from apple branches had the ability to absorb NO3−-N with an absorption capacity of 3.51 mg·g−1. The absorption data fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…In order to optimize the use of adsorbents, previous studies have suggested modeling interactions between biochar and N during the adsorption process (He et al, 2023) Langmuir equation:…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…In order to optimize the use of adsorbents, previous studies have suggested modeling interactions between biochar and N during the adsorption process (He et al, 2023) Langmuir equation:…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…The physical adsorption of nitrate N in the pores of biochar cannot be ruled out, and the physical adsorption of nitrate in carbonized matrices could be a mechanism to prevent nitrate losses through leaching in soils treated with biochar [11]. Thus, the adsorption of nitrate in biochars could be a suitable strategy to reduce N losses in the soil-plant system [12]. The use of biochar-N composites increased the nutrient use efficiency by corn in 44% over N from urea [11].…”
Section: Introductionmentioning
confidence: 99%